Development of a Healthy Lifestyle Promotion Protocol for Individuals with Binge Eating - Zamani, Sedigheh; Shahpouri Arani , Mahbod (KMAN Counseling & Psychology Nexus, 2026)
The objective of this study was to develop and validate a comprehensive, evidence-based protocol for promoting a healthy lifestyle among individuals with binge eating, grounded in empirical data and aligned with contemporary behavioral and psychological models. This applied mixed-methods study followed a sequential exploratory design. In the qualitative phase, semi-structured interviews were conducted with adults with binge eating from Tehran using purposive sampling until theoretical saturation was achieved, and data were analyzed through thematic analysis. In the quantitative phase, the extracted components were examined in a larger sample to assess content validity and internal consistency, and the finalized protocol was structured into a session-based intervention model. Thematic analysis yielded six core domains of healthy lifestyle promotion: psychological self-regulation, eating behavior restructuring, physical activity integration, stress and sleep management, social and environmental support, and meaning and motivation. Content validity indices and ratios exceeded acceptable thresholds for all components, and reliability analysis demonstrated strong internal consistency, with high Cronbach’s alpha coefficients for individual domains and excellent overall protocol reliability. The findings support the conceptualization of binge eating as a multidimensional lifestyle-related condition and indicate that the developed protocol is theoretically coherent, empirically grounded, and psychometrically sound. The protocol provides a structured yet flexible framework that integrates emotional, behavioral, and lifestyle components, offering a promising approach for promoting sustainable healthy lifestyle change among individuals with binge eating.